Evaluation of small antenna based si-substrate with heat process for wireless sensor applications - Pinsakul, Atcharaporn; Pathoumvanh, Somsanouk; Promwong, Sathaporn (My University, 2020)
A silicon substrate small patch antenna for small antenna is using cavity model and method of moment are analyse antenna. Dope Silicon substrate with gold is having the resistivity over 106. It's good performance for monolithic patch antenna. Calculated numerical results are in awesome agreement with the computed results.
Keywords: Microstrip patch antenna; Semiconductor; Silicon substrate; Small antenna; Wireless sensor